Robust tuning of PFC (Predictive Functional Control) based on first- and aperiodic second-order plus time delay models. (June 2017) - Zabet, Khaled; Haber, Robert
Highlights: It is shown that PFC algorithm for a delayed stable process has the structure of a Smith predictor. PFC was extended by a first-order low-pass filter to improve the robustness against uncertainty of the process parameters. The focus was on improving the robustness for stable processes having first- or second-order plus dead time model. The robustifying filter was designed analytically for time delay, time constant and static gain mismatch. The proposed robust design of PFC was applied successfully for controlling a pilot plant. Abstract: Robust tuning is presented for PFC (Predictive Functional Controller) for stable non-integrative processes modelled as FOPDT and aperiodic SOPDT (First- and Second-Order Plus Dead Time) models, assuming stepwise changes in the reference or disturbance signal. The robustness is improved by using a first-order filter. The filter time constant is designed in the knowledge of the uncertainty of the model parameters (static gain, time constants and time delay). Both simulation results and the control of a laboratory pilot plant are presented.